Arab Countries in Transition : Economic Outlook and Key Challenges. (Policy Papers; Policy Paper ;, 2013)
In an environment of heightened socio-economic tensions, regional insecurity, and strained public finances, the Arab Countries in Transition (ACTs) 1 face the difficult task of delivering on the expectations for jobs and growth. Despite patchy improvements in some countries, economic growth remains subdued, private investment is weak, and external and fiscal buffers are running low. Fostering social cohesion and avoiding a downward spiral of economic and political malaise calls for urgent implementation of economic reforms and coordinated support from the international community.